Evolutionary Insights Based on SNP Haplotypes of Red Pericarp, Grain Size and Starch Synthase Genes in Wild and Cultivated Rice - Singh, Nisha; Singh, Balwant; Rai, Vandna; Sidhu, Sukhjeet; Singh, Ashok K.; Singh, Nagendra K. (Frontiers in Plant Science, 2017)
The origin and domestication of rice has been a subject of considerable debate in the post-genomic era. Rice varieties have been categorized based on isozyme and DNA markers into two broad cultivar groups, Indica and Japonica. Among other well-known cultivar groups Aus varieties are closer to Indica and Aromatic varieties including Basmati are closer to Japonica, while deep-water rice varieties share kinship to both Indica and Japonica cultivar groups. Here, we analyzed haplotype networks and phylogenetic relationships in a diverse set of genotypes including Indian O. nivara / O. rufipogon wild rice accessions and representative varieties of four rice cultivar groups based on pericarp color (Rc), grain size (GS3) and eight different starch synthase genes (GBSSI, SSSI, SSIIa, SSIIb, SSIIIa, SSIIIb, SSIVa and SSIVb). Aus cultivars appear to have the most ancient origin as they shared the maximum number of haplotypes with the wild rice populations, while Indica, Japonica and Aromatic cultivar groups showed varying phylogenetic origins of these genes. Starch synthase genes showed higher variability in cultivated rice than wild rice populations, suggesting diversified selection during and after domestication. O. nivara / O. rufipogon wild rice accessions belonging to different subpopulations shared common haplotypes for all the ten genes analyzed. Our results support polyphyletic origin of cultivated rice with a complex pattern of migration of domestication alleles from wild to different rice cultivar groups. The findings provide novel insights into evolutionary and domestication history of rice and will help utilization of wild rice germplasm for genetic improvement of rice cultivars.